Avaliação molecular de sementes de café submetidas à criopreservação - Veloso, Juliana Souza (2016)
Coffee seeds present low longevity and sensitivity to desiccation, which limits their storage in conventional germplasm banks. As alternative method for this conservation, storage in ultralow temperatures, using liquid nitrogen, have been studied. Howeve r, the molecular changes that occur in coffee seeds stored under these conditions are not yet entirely known. Therefore, with this work, we aimed at evaluating the expression of genes from coffee seeds submitted to different cryopreservation protocols in order to expand the knowledge of the effects of cryopreservation over the viability of these seeds at molecular level and to aid in understanding the physiological, biochemical and molecular results. The expression of target genes varies according to drying, pre-cooling and reheating time methodologies. The use of sodium chloride (75% UR) for drying and/or the absence of pre-cooling results in a greater expression of the genes isocitrate lyase, esterase, dehydrin and apetala 2 in the seeds of Coffea arabica L. cv. Catuaí amarelo IAC 62 when compared to the other drying and pre-cooling methodologies. The use of ammonium sulfate (85% UR) for drying and/or pre-cooling up to -50 °C provides greater expression of genes telomerase, apoptosis inhibitor and DNA methylase in the seeds of Coffea arabica L. cv. Catuaí amarelo 62 when compared to the other drying and pre-cooling methodologies or in the absence of pre-cooling. Genes telomerase, apoptosis inhibitor and DNA methylase, as well as genes ascorbate peroxidase, superoxide dismutase and peroxidase present similar expression pattern.